Root growth and nutrient flux of cowpea under field condition - ADEPETU, J. A. (Faculty of Agriculture, University of Ife, 2015)
Field studies were conducted on an Egbeda soil series (Oxic Paleustalf) to determine the root length, root surface area and the nutrient flux into cowpea root at five days intervals of growth from 5 to 50 days after emergence. In companion study, a solution culture study was conducted in the greenhouse to determine if information from greenhouse investigations are valid indices of field situations regarding the characteristic changes in root growth with age of cowpea. A speculation was made from the result of the field study concerning the best time of P and K fertilizer application for greatest yield. To test the validity of this speculation a study was set up on the field whereby cowpea dry pod weights produced from applying the fertilizer 10, 20. 30, 40 arid 50 days after emergence were determined. Cowpea root length increased exponentially with plant age between 5 and 50 days after emergence, even though the relationship tend to be linear at the very young growth stages. The extent of agreement between root growth on the field and in the greenhouse suggests that solution culture research results could be applied to field conditions. Nutrient flux was greatest when the plant was 5 days old, decreased rapidly with age of the plant to about 28 days old, remained constant for the next few days, then increased agilin and stayed relatively high between 40 and 50 days. Dry pod yield obtained by fertilizing cowpea with P and K of 40 days old was significantly greater (P4 0.5) than yields from 20.30 and 50 days application dates, but not significantly superior (P> 0.5) to yield from applying fertilizer at 10 days. It is concluded that availability of P and K to cowpea root in the soil is critical to optimum pod yield at the early vegetative growth stage (about 10 days after emergence) and during the early flowering stage, but apparently more critical at the early flowering than the young growth stage.